2018
DOI: 10.1038/s41598-018-29695-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-negligible Water-permeance through Nanoporous Ion Exchange Medium

Abstract: While the water impermeable constraint has been conventionally adopted for analyzing the transport phenomena at the interface of electrolyte/nanoporous medium, non-negligible water-permeance through the medium results in significant effect on ion and particle transportation. In this work, a rigorous theoretical and experimental analysis of the water-permeance effect were conducted based on a fully-coupled analytical/numerical method and micro/nanofluidic experiments. The regime diagram with three distinctive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 38 publications
(24 reference statements)
1
23
0
Order By: Relevance
“…Both velocities (U DP and U μ ) are proportional to the time −1/2 [14]. Thus, they were plotted as a straight line with a negative slope in log scale graph as shown in Fig.…”
Section: Mechanism Of Spontaneous Separation Methods In μPadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both velocities (U DP and U μ ) are proportional to the time −1/2 [14]. Thus, they were plotted as a straight line with a negative slope in log scale graph as shown in Fig.…”
Section: Mechanism Of Spontaneous Separation Methods In μPadsmentioning
confidence: 99%
“…Our previous work presented the spontaneous preconcentration (or selective preconcentration) method in microfluidic chip with leveraging convective flow through microchannel over diffusiophoresis induced by imbibition and ion exchange of ion exchange medium, respectively [13][14][15][16][17][18]. Especially, we had demonstrated that the velocity of the convective flow by the imbibition of the medium deviated from original Darcy's law using non-uniformly patterned ion exchange medium, but this work has the limitation of time-consuming and complex process [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the width of hydrogel was almost unchanged at pH = 3.5, while it expanded by 23% after 1 h in the solution of pH = 5.5 as shown in Figure 6a. When the swollen hydrogel blocked a microchannel, the configuration of microchannel was changed into micro-nano-micro-connection because the hydrogel possesses a number of nanopores inside [26,29,51]. Consequently, one can expect ICP phenomenon with the swollen hydrogel.…”
Section: Nanofluidic Sensing Of Ph Stimulationmentioning
confidence: 99%
“…The reason why it slightly dropped in case of pH = 3.5 was that ICP also formed when a micro-and a nano-junction coexist in parallel [55][56][57][58]. While one expects a higher initial current in a micro-micro-micro-connection than one in a micro-nano-micro-connection by considering cross-sectional area, it involves complex interactions such as Donnan concentration of nanoporous material [51,59], surface charge of microchannel [13], the concentration of electrolyte (i.e., Debye length) [2,55], and the transversal dimension of hydrogel itself, etc. Thus, normalized current values with respect to each initial current value were plotted in the inset of Figure 6c.…”
Section: Nanofluidic Sensing Of Ph Stimulationmentioning
confidence: 99%
“…Diffusiophoresis is the electrochemical phenomenon that a charged particle moved from low concentration region to high concentration region along a concentration gradient in the case of electrolyte solution such as KCl solution where each diffusivity is almost identical so that one can ignore induced electrophoresis. This concentration gradient can be generated by two miscible liquids of different concentrations [1,2] or by ion exchange [3][4][5]. Especially, cation exchange phenomenon can occur near a nanoporous medium having protons with high diffusivity if the medium meets the solution with non-protonic cation, which means that the concentration gradient would be spontaneously generated by cations' difference of diffusivity without any external forces [4].…”
Section: Introductionmentioning
confidence: 99%